Ka-band satellite communication experiments and rain attenuation measurements using WINDS - Fukuchi, H.; Abe, N.; Takahashi, T.; Asai, T. (2009 7th International Conference on Information, Communications and Signal Processing, 2009)
Domestic and international experiments using WINDS under the guidance of ARIB are introduced. Super-Hivision signal transmission experiment was carried out in May 2009 under the collaboration between NICT and NHK. In this experiment Super-Hivision signal is transmitted from Sapporo to Tokyo using WINDS. The Ku- and Ka-band satellite signals reception system for Earth-space path attenuation characteristics analysis at Tokyo Metropolitan University (TMU) is shown. In this system, WINDS TDMA signal is received with very short time period using by measuring each TDMA slot signal levels.